Chapter 1.2 History of Research Administration/Management in North America - Kris Monahan; Toni Shaklee; Deborah Zornes (Emerald Publishing Limited, 2023)
In North America, the profession known as `research management' elsewhere across the globe, is often known as `research administration' and encompasses the activities and work associated with developing, administering, accounting for and complying with sponsor requirements, guidelines, procedures, and laws relating to externally funded projects. In the United States and Canada, the expansion of respective federal government agencies and programmes was the major factor for the need and growth of the research administration profession. Initially, administrative and business staff often administered research funding, however over the decades, a fully-fledged profession has evolved with distinct specialisations. Both the United States and Canada now have maturing professions and professional societies to organise and advance research administration. This chapter outlines the chronological origins, growth, and professionalisation of research administration in North America, with a focus on the United States and Canada. Mexico has not yet evolved a formalised research administration infrastructure.
10.1108/978-1-80382-701-820231004; 10.1108/978-1-80382-701-820231004; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262